Wave climate study in the southwest coast of the Black Sea - Ari, H. A.; Yuksel, Y.; Cevik, E. Oezkan; Sahin, C.; Ayat, B. (INTERNATIONAL SOCIETY OFFSHORE& POLAR ENGINEERS, 2006)
Wave information is needed over long periods to obtain the wave climate in the respective research area especially for the coastal engineering objectives. Generally measured wave data is available for short periods since the measurement of them is expensive and time consuming. Due to the lack of this kind of data, it is necessary to develop approaches to extend time series of wave parameters from measured wave data. Wind parameters can be obtained for much longer periods and on the basis of these data this approaches may be gathered. In the present work, directional wave measurements were carried out at the site by an acoustic and pressure type wave gauge for a certain period. Both measured (wave gauge data) and predicted wave (using wind data) input data were evaluated and compared at Karaburun coastal region at the southwest Black Sea.
Keywords: wave measurement; wind-wave correlation; Black Sea; Engineering